666 Itineraries through the split city - Lanceros, Patxi (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The drama of politics runs through the Divine Comedy from beginning to end, and is one of its main threads: forms of government, social habits, virtues, passions and political vices are censored, analysed and rigorously evaluated throughout the whole of the great work. The sixth cantos of the three parts of the Commedia —Inferno, Purgatorio and Paradiso— deal with this drama in an intense way: like concentric circles, they cover an increasingly larger space: Florence, Italy, the —always diffuse— Empire (i.e. the politically organised world, the oecumene). This article analyses these cantos from a perspective that, insistently, gives a basis and unity to the whole: the division of the city, the civil war.
Keywords: Politics; War; City; Justice; Providence